Processing Impact on Nutritional, Antinutritional, and Phytochemical of Fenugreek Seeds (Trigonella Foenum-Graecum L.) - Adhikari, Babita; Rai, Shonu (Himalayan Journal of Science and Technology, 2021)
Phytate and tannin are more pronounced antinutrients limiting the nutritional quality of fenugreek. The impact of roasting (130±5°C for 7 minutes), soaking (12 hrs. at room temperature) and germination (72 hrs. at 25°C) on bioactive compounds (polyphenol and antioxidant activity), nutritional and anti-nutritional compounds (phytate and tannin) in Fenugreek were studied. Experimental data were analyzed using the software GenStat 12th Edition. Protein increased significantly (p